Interpreting Symbols of Cultural Identity Jatiwangi Clay - Liza Dwi Ratna Dewi; Eko Putra Boediman (LONTAR: Jurnal Ilmu Komunikasi, 2024)
In 2012, the Central Government of the Republic of Indonesia projected the West Java Strategic Industrial Zone called the Rebana Triangle with 3 points: Cirebon City, Subang Regency, and Majalengka Regency. Since then, a large wave of modern industrialization has entered this area and affected all aspects of community life, including the threat to the existence of local cultural identity. This research aims to explore the meanings of 3 cultural symbols produced by the Jatiwangi Art Factory (JAF), a community of artists based in the Jatiwangi District, Majalengka Regency. Stuart Hall's concept of Cultural Identity serves as the reference basis, and Roland Barthes' Semiotics is used as the research analysis method. The research subjects are JAF, and the research objects are the 3 cultural symbols created by JAF. Data collection was conducted through informal discussions, field observations, the internet, and literature studies from 2000 to 2023. The results of the research show that: the Rampak Genteng Festival is a process of forming strong cultural defenses in mental, geographical, and political spaces. Clay Music is a dominant process of forming defenses in mental space. Meanwhile, Terakota City is the formation of cultural identity defenses in geographical, political, social, and economic spaces.